Addressing the self-directed learning culture gap in Kenya’s competency-based Curriculum Junior School integrated Science post-COVID-19 - Ongesa, Cosmas Masega; Mwinzi, Joseph; Gunga, Samson; K’Odhiambo, Atieno Kili (European Scientific Journal, ESJ, 2024)
There are varied bodies of research on self-directed learning (SDL), a few of these studies have been done about developing a self-directed learning culture (SDLC), especially in Competency Based Curriculum (CBC) junior schools. The study mainly focuses on how the curriculum reforms for Kenyan CBC junior school integrated science and the current theoretical instructional model have promoted the development of SDLC. The data is gathered, examined using the Kantian critical judgment theory model, and evaluated using the standard reflective self-directed instructional model (RSIM) by Mentz, Laubscher, and Olivier (2021). Key theoretical premises, sub-themes, and themes are developed using the categories scrutinized and analyzed. According to the analysis, no education reform has suggested that schools, teachers, and students in Kenya’s CBC junior school should develop the common themes, sub-themes, and learning strategies of SDLC. A novel instructional model that supports the development of the SDLC is thus needed.